2000
DOI: 10.1080/713659421
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and trends in alcohol‐related hospitalizations in Victoria, Australia, 1987/88–1995/96

Abstract: The objective of this study was to examine patterns and yearly trends in alcohol-related hospitalization rates during the period 1987/88-1995/96 for men and women living in metropolitan and rural/remote Victoria. Alcohol-related hospitalizations were extracted from the Victorian Inpatient Minimum Dataset (VMD) for the years 1987/88-1995/96 (public hospitals) and 1993/94-1995/96 (private hospitals), and adjusted by the appropriate aetiological fractions. Sex-specific age-adjusted rates we expressed per 10000 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Using alcohol attributable fractions, Ridolfo and Stevenson 9 estimated that harmful/hazardous alcohol consumption contributed to 43,033 hospital separations in 1997/98 (total hospital separations in 1997/98 totalled 5,563,074, 10 accounting for less than 1% of total separations. Alcohol attributable fraction calculations for Victoria show similar results with an estimated that 1% of hospitalisations attributable to harmful alcohol use 11 . Estimates of alcohol involvement in hospital admissions from the US vary widely, with estimates ranging from 7 to 70% of general admitted patients 12 …”
supporting
confidence: 58%
“…Using alcohol attributable fractions, Ridolfo and Stevenson 9 estimated that harmful/hazardous alcohol consumption contributed to 43,033 hospital separations in 1997/98 (total hospital separations in 1997/98 totalled 5,563,074, 10 accounting for less than 1% of total separations. Alcohol attributable fraction calculations for Victoria show similar results with an estimated that 1% of hospitalisations attributable to harmful alcohol use 11 . Estimates of alcohol involvement in hospital admissions from the US vary widely, with estimates ranging from 7 to 70% of general admitted patients 12 …”
supporting
confidence: 58%
“…6 Women living in rural or remote areas also had a higher rate of hospitalisations because of alcohol-related injury. 6 Alcohol-related emergency presentations for assault and violence within rural Victoria continue to increase faster than the Victorian average for the past three years (Fig. 1).…”
Section: Hospitalisationmentioning
confidence: 98%
“…6 People within rural areas who drink at a medium/high-risk level report significantly more problems with mobility, pain/discomfort and anxiety/ depression than metropolitan counterparts. 27 Those drinking at very-high-risk levels were reported to experience lowered health outcomes in relation to self-care, usual activities, pain/discomfort and anxiety/depression compared with people in metropolitan areas.…”
Section: Morbiditymentioning
confidence: 99%
See 1 more Smart Citation
“…We used the GenACIS (Gender, Alcohol and Culture: an International Study) survey instrument that has been administered to around 40 countries. In contrast to other countries, survey data have only rarely been used to examine the prevalence of the adverse consequences of drinking among Australian drinkers, with most work in Australia focused on administrative data on outcomes such as hospitalizations and deaths (e.g., Jonas, Dietze, Rumbold, Hanlin, Cvetkovski, & Laslett, 1999;Hanlin, Jonas, Laslett, Dietze, Rumbold, & Cvetkovski, 2000). A previous report on the social location of drinking in the GenACIS sample has shown that risky patterns of drinking such as consuming six or more Australian Standard Drinks (ASD, 10 g pure alcohol) on any one occasion (hereafter, Risky Single Occasion Drinking, RSOD) were generally more prevalent among men than women (Matthews, 2008).…”
mentioning
confidence: 98%